EFFECT OF UV-B RADIATION ON LIPID PEROXIDATION OF TION OF THYLAKOID MEMBRANES OF CYANOBACTERIUM SYNECHOCOCCUS SYNECHOCOCCUS 6301 - K. GIRIDHAR KUMAR; P. KIRAN MAYI; S. D. S. MURTHY (The Bioscan, 2010)
The objective of the present study was to characterize the effect of UV-B radiation on thylakoid lipid peroxidation in the cyanobacterium Synechococcus 6301. The UV-B radiation caused gradual enhancement in the lipid peroxidation of thylakoid membrane. To analyze the protective mechanism against lipid peroxidation 2 mM ascorbate was used as reducing agent in reaction mixture before exposed to UV-B radiation. The studies explained that ascorbate acted as potent reducing agent during peroxidation of thylakoid membranes. To correlate the lipid peroxidation with photosystem II catalyzed electron transport, the results indicated the inverse relationship between photosystem II photochemistry and lipid peroxidation.